PERKEMBANGAN ASPEK ILMU PENGETAHUAN DALAM INDUSTRI PERKEBUNAN DI SUMATRA TIMUR 1863–1942 - Itawan, Devi (Paradigma: Jurnal Kajian Budaya, 2022)
This study aims to reveal the relationship between science and the plantation industry on colonial expansion in East Sumatra. In this study, science is regarded as a colonial construction, which in the context of East Sumatra was used as a tool for colonial expansion, supporting the process of surplus accumulation through the plantation industry. This research applied the historical method, in which analysis was carried out on primary sources such as colonial scientific publications, travelogues, newspapers, and magazines. An examination of these primary sources was conducted by analyzing the text and the context. The decolonial perspective provides an analytical framework for disentangling the colonial relations and conditions behind every scientific project and its publication in East Sumatra. It turns out that the rationale of colonial science was formulated in favor of colonial plantation industry. To conclude, it is apparent that the relationship between science and the plantation industry was intense and symbiotic. The plantation industry was able to thrive with the support of scientific rationality, and conversely, geography, geology, agronomy and health flourished with the financial support from plantation companies.